The diabetogenic mouse MHC class II molecule I-A(g7) is endowed with a switch that modulates TCR affinity - Yoshida, Kenji (American Society for Clinical Investigation, 2010)

(untitled)
Genetic susceptibility to autoimmunity is frequently associated with specific MHC alleles. Diabetogenic MHC class II molecules, such as human HLA-DQ8 and mouse I-A(g7), typically have a small, uncharged amino acid residue at position 57 of their β chain (β57); this results in the absence of a salt bridge between β57 and Argα76, which is adjacent to the P9 pocket of the peptide-binding groove. However, the influence of Argα76 on the selection of the TCR repertoire remains unknown, particularly when the MHC molecule binds a peptide with a neutral amino acid residue at position P9. Here, we have shown that diabetogenic MHC class II molecules bound to a peptide with a neutral P9 residue primarily selected and expanded cells expressing TCRs bearing a negatively charged residue in the first segment of their complementarity determining region 3β. The crystal structure of one such TCR in complex with I-A(g7) bound to a peptide containing a neutral P9 residue revealed that a network of favorable long-range (greater than 4 Å) electrostatic interactions existed among Argα76, the neutral P9 residue, and TCR, which supported the substantially increased TCR/peptide-MHC affinity. This network could be modulated or switched to a lower affinity interaction by the introduction of a negative charge at position P9 of the peptide. Our results support the existence of a switch at residue β57 of the I-A(g7) and HLA-DQ8 class II molecules and potentially link normal thymic TCR selection with abnormal peripheral behavior.